NDNS performance with variation of topology and prefix on named data networking - Daffa, Muhammad; Yovita, Leanna Vidya; Wibowo, Tody Ariefianto (Universitas Telkom, 2023)
NDNS is DNS embedded in Named Data Network (NDN) architecture as a distributed database system to support NDN caching and know the content's location. In this research, the simulation performed using two topologies, Abilene and PAN-Europe with changes to their prefixes. This simulation conducted to see performance of NDNS with minimal ability to cache on NDN router or Caching Resolver. From simulation results, the variation of prefix at Second Level Domain and Top Level Domain there is no difference in average delay in both topologies, namely 1% increase in average delay as the variation of prefix increases. There is a decrease in the Cache Hit Ratio by 0.16% (Abilene) and 0.18% (PAN-Europe) because the probability of getting cached data decreases as the prefix varies. In the change in interest frequency, there is an increase of 0.4% in average delay and the Cache Hit Ratio decreases by 0.08% in both topologies as the frequency of interest per second increases. NDNS with cache in Router and Caching Resolver get 43% lower average delay (Abilene) and 44% (PAN-Europe) than NDN with cache in Router and 57% lower (Abilene) and 60% (PAN-Europe) than NDNS with cache in Caching Resolver only.